When we think on information systems in a company or an administration, what we think? - Cobarsí-Morales, Josep (Anuario ThinkEPI, 2012)
In conceptualizing information systems always there have been a dilemma between two options: either use them as mere automation tool over the existing situation, or convert it in an enhancer element, i.e. a radical transformation facilitator. A historical example is examined and future trends in line to illustrate the possibilities of an enhancing choice are suggested.